Tumors in the parotid are not relatively more often malignant in children than in adults. Issue 8 (August 2015) - Stevens, E.; Andreasen, S.; Bjørndal, K.; Homøe, P.
Abstract Introduction Tumors of the parotid gland in children are rare and very little data has been published regarding the incidence of these tumors. We present a nationwide survey on this topic. Methods Data regarding benign and malignant tumors in the parotid gland in children from January 1st, 1990 to December 31st, 2005 in Denmark was collected retrospectively from nationwide registries. This generated 61 patients for inclusion in this study. Results 85% of the tumors were benign and the malignant tumors made up the last 15%. The most common of the malignant tumors was the acinic cell carcinoma (n = 4) followed by the mucoepidermoid carcinoma (n = 3) and adenoid cystic carcinoma (n = 2). The overall female-to-male ratio was 1.18, with a ratio of 1.08 and 2.0 in the benign and malignant groups, respectively. At the end of follow-up (August 1st, 2014) two patients had died, one with adenoid cystic carcinoma and one with mucoepidermoid carcinoma. Both patients had perineural invasion and involved resection margins at presentation. The incidence was 0.12 and 0.53 per 100, 000 children of the malignant and benign tumors, respectively. Conclusion Pleomorphic adenomas were the predominant neoplasm in the parotid gland in children. The most frequent of the malignant tumors was the acinic cell carcinoma, which is in contrast to previous studies. The proportion of malignant-to-benign parotid gland tumors is in contrast to earlier study reports not higher in children than in adults.